Digital tool integration, biodiversity, and the potato value chain in Kenya: Results from a baseline survey - Boukaka, Sedi Anne; Geoffrey, Baragu; Azzarri, Carlo (International Food Policy Research Institute, 2025)
Potato farmers in Kenya grapple with various challenges along the value chain, including limited access to quality planting materials such as seeds and fertilizers, insufficient storage and postharvest handling facilities, fluctuating market prices, and unreliable market information systems. For women and youth, these challenges are further exacerbated by persistent social gaps in the agriculture sector. Digital tools can play a vital role in addressing these challenges by providing access to valuable agricultural information, weather forecasts, and best practices that help farmers make informed decisions and improve crop management. However, challenges persist in digital tool adoption within agricultural value chains in sub-Saharan Africa. This study assesses the impact of digital tool adoption and support on socioeconomic and agriculture-related outcomes in Kenya’s potato value chain. It piggybacks on an ongoing digital tool integration program, Business Development and Coaching (BDEC), conducted by the Farm to Market Alliance (FtMA), which targets agripreneurs in Farmer Service Centers (FSCs). By comparing a treatment group that receives this training with a control group continuing business as usual, the study evaluates the effects of agripreneurs’ adoption and expanded use of digital tools on farmers’ agriculture based livelihoods, income generation, and job creation metrics, with a focus on youth employment and gender disparities.